Two Different Views on Grief and Agony as Mental Pains In Emily Dickinson's Poems - Naila Amilia Satria (Vivid: Journal of Language and Literature, 2019)
This research looks at two poems of Emily Dickinson which are “I Measure Every Grief I Meet” and “I like a look of Agony”. The goal of this research is to show different views on grief and agony as mental pains in order to gain a better understanding of the two poems. The writer applies New Criticism approach and uses comparative method in order to get evidences that are needed. The text focuses on pointing out different views on grief or mental pain through attitudes of the speakers in each poem by analyzing the two poems stanza-by-stanza. This paper affirms that even though the two poems have same theme which are grief and agony or mental pain, the attitude of each speaker towards these issues is significantly different. In "I Measure Every Grief I Meet", the speaker shows that they are full of compassion in observing their surroundings, they show sympathy and concern on people's feeling. The speaker admits that find comfort in knowing others also feel grief as they do but they do not see it as something beneficial to them so that they can take advantage from those who are in grief or experiencing physical pain. In "I Like a Look of Agony", the speaker is being harsh and selfish because they do not care of the condition of those who are in agony. The speaker shows no sympathy but the fact that this is something that benefits them so that they can find comfort in witnessing the agony of others.